Problematic gaming behaviour and health-related outcomes: A systematic review and meta-analysis. (January 2020) - Männikkö, Niko; Ruotsalainen, Heidi; Miettunen, Jouko; Pontes, Halley M; Kääriäinen, Maria
This systematic review and meta-analysis aimed to investigate the interplay between problematic gaming behaviour and health-related outcomes at different developmental stages. A total of 50 empirical studies met the specified inclusion criteria, and a meta-analysis using correlation coefficients was used for the studies that reported adverse health implications regarding the impact of problematic gaming behaviour on depression, anxiety, obsessive–compulsive disorder and somatisation. Overall, the results suggested that problematic gaming behaviour is significantly associated with a wide range of detrimental health-related outcomes. Finally, the limitations of this review alongside its implications were discussed and considered for future research.